1986
DOI: 10.1073/pnas.83.21.8077
|View full text |Cite
|
Sign up to set email alerts
|

Action mechanism of ABC excision nuclease on a DNA substrate containing a psoralen crosslink at a defined position.

Abstract: Many carcinogenic as well as chemotherapeutic agents cause covalent linkages between complementary strands of DNA. If unrepaired, DNA crosslinks are blocks to DNA replication and transcription and therefore represent potentially lethal lesions to the cell. Genetic studies of Escherichia coli have demonstrated that the repair enzyme ABC excision nuclease, coded for by the three unlinked genes, uvrA, uvrB, and uvrC, plays a crucial role in DNA crosslink repair. To study the molecular events of ABC excision nudea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
194
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(205 citation statements)
references
References 35 publications
(26 reference statements)
10
194
0
1
Order By: Relevance
“…The protein binds preferentially to damaged DNA, with a discrimination factor for UV lesions of -103. Interestingly, this is the same order of magnitude of damaged site discrimination as found for the E.coli UvrA protein (Seeberg and Steinum, 1982;Van Houten et al, 1987;Mazur and Grossman, 1991). Neither XP-A protein nor UvrA can introduce nicks into DNA on its own.…”
Section: Function Of the Xp-a Proteinsupporting
confidence: 58%
“…The protein binds preferentially to damaged DNA, with a discrimination factor for UV lesions of -103. Interestingly, this is the same order of magnitude of damaged site discrimination as found for the E.coli UvrA protein (Seeberg and Steinum, 1982;Van Houten et al, 1987;Mazur and Grossman, 1991). Neither XP-A protein nor UvrA can introduce nicks into DNA on its own.…”
Section: Function Of the Xp-a Proteinsupporting
confidence: 58%
“…Measurements of psoralen-induced DSBs by pulsed field gel electrophoresis showed a larger reduction in a triple rad2 rad6 rad52 mutant strain than in the single rad2 mutant, indicating a role for other repair epistasis groups in DSB formation (19). Alternatively, DSBs may not be the only recombinogenic intermediates; for instance, in bacteria recombination is initiated by single strand gaps opposite psoralen adducts (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…There are at least two possible processes by which a crosslink can be removed from the DNA. In one model, the crosslink is completely repaired by 1) incising one strand, 2) filing in the gap, and then 3) removing the resultant crosslinked oligomer from the other strand by homologous strand exchange (27) (25). Furthermore, it was shown that the most frequent DNA adduct induced by cisplatin, the intrastrand d(GpG) platinum crosslink is poorly repaired in human cell extracts (30,31).…”
Section: Discussionmentioning
confidence: 99%